Higher education studies in the restive areas of Thailand’s Southern insurgency: a comparison of resilience among students at the Pattani campus and a nearby province - Chonnakarn Jatchavala; Arnont V (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
The Prince of Songkla University, Pattani campus is located within the restive areas of Southern Thailand’s insurgency. The violent situations have been continuingly deteriorating since 2004, whilst local civilians; including young people, have undergone different forms of mental distress. Hence, this cross-sectional survey aimed to compare levels, characteristics and associated factors of resilience among university students at the Pattani campus, located in the restive area of Southern Thailand’s insurgency, and a nearby province (Hatyai campus). The study was conducted between 8th August, 2018 and 8th October, 2018, at both Prince of Sonkla University, Pattani and Hatyai campuses. All of the participants completed the personal information, and Thai resilience questionnaires (Thai-RQ) by themselves. The data were analysed using the R program, for both descriptive statistics and logistic regression. Most of the 443 students, who studied at Prince of Songkla University, Pattani campus were females (80.3%) and Muslims (76.3%). Most of them were at a normal level (55.7%), within the domain of resilience, with the highest prevalence, being coping strategy (75.9%). No significantly statistical difference of levels, or characteristics of resilience were found between the two campuses. Satisfaction towards: university teaching, age, religion and birth order were also significantly associated to resilience among university students in the restive area. However, only gender and satisfaction towards university teaching were found in the non-restive campus.